Montenegro : Financial Sector Assessment Program-Financial Crisis Preparedness and Management-Technical Note. (IMF Staff Country Reports; Country Report ;, 2016)
This paper provides assessment of the crisis preparedness and management framework of Montenegro. The banking sector dominates the financial system and accounts for about 90 percent of financial system assets, equivalent to about 93 percent of GDP as of June 2015. In 2010 the Financial Stability Council (FSC) was established to maintain financial system stability and avoid financial distress. FSC members are the Central Bank of Montenegro (CBM) governor (chair), the minister of finance, the president of the Insurance Supervision Agency Council, and the Securities and Exchange Commission president. The CBM functions as the de facto resolution authority for banks.